2017
DOI: 10.3164/jcbn.16-120
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein improves insulin resistance in skeletal muscle by promoting the translocation of GLUT4

Abstract: As the beneficial effects of the Mediterranean diet on human health are well established, the phenolic compounds in olive oil have been gaining interest. Oleuropein, a major phenolic compound in olives, is known to reduce the blood glucose levels in alloxan-induced diabetic rats and rabbits, however, its effect on type 2 diabetes caused by obesity is not clear. The purpose of this study is clarifying the effect of oleuropein on the glucose tolerance in skeletal muscle under the condition of lipotoxicity caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 47 publications
(49 reference statements)
3
31
0
Order By: Relevance
“…In T2D mice fed with OPAICE diet, a phenolic extract containing 35% w/w oleuropein prevented weight gain and significantly reduced nonfasting blood glucose levels and hyperglycemia following glucose loading (Murotomi et al, ). Oleuropein also reduced fasting blood glucose in high‐fat diet‐fed mice (Fujiwara et al, ). Oleuropein has a local action on the intestinal wall where it was observed to inhibit intestinal maltase and sucrase enzymes.…”
Section: Role Of Oleuropein In Treatment Of Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…In T2D mice fed with OPAICE diet, a phenolic extract containing 35% w/w oleuropein prevented weight gain and significantly reduced nonfasting blood glucose levels and hyperglycemia following glucose loading (Murotomi et al, ). Oleuropein also reduced fasting blood glucose in high‐fat diet‐fed mice (Fujiwara et al, ). Oleuropein has a local action on the intestinal wall where it was observed to inhibit intestinal maltase and sucrase enzymes.…”
Section: Role Of Oleuropein In Treatment Of Metabolic Syndromementioning
confidence: 99%
“…Oleuropein administered alone improved glucose tolerance (Khalili et al, 2017;Poudyal et al, 2010) and reduced insulin resistance (S.W. Kim et al, 2014) or insulin sensitivity (Lepore et al, 2015) and, on C2C12 myoblast cells, promoted translocation of GLUT4 into the cell membrane via AMPK activation and MAPK's but not PI3 kinase (phosphatidylinositol 3-kinase)/protein kinase B (Akt; Fujiwara et al, 2017, Hadrich, Mahmoudi, et al, 2016. Oleuropein has been implicated to improve postprandial glycemic profile via hampering NOX 2 -derived oxidative stress (R. Carnevale et al, 2018).…”
Section: Antidiabetic Effects Of Oleuropeinmentioning
confidence: 99%
“…In last years, the importance of the antioxidant activity of 3,4-DHPEA-EA [9][10][11] and its derivatives at the level of skeletal muscle has emerged [12][13][14]. Skeletal muscle is a tissue in which ROS play particular importance: at low concentrations ROS act as signaling molecules in signal transduction pathways; instead at high concentrations they can result in oxidative stress and muscular atrophy [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the natural molecules 3,4-DHPEA-EA and its derivatives seem to play an important role in regulation of skeletal muscle homeostasis [12,13]. In particular, it has been demonstrated that oleuropein induces an increase of glucose uptake through the activation of AMP-activated protein kinase (AMPK) and consequent increase in GLUT4 translocation at the cell membrane [13,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation